Sarcoidosis as unusual cause of massive pleural effusion. (2015) - Joshi, Sharad; Periwal, Pallavi; Dogra, Vikas; Talwar, Deepak
Abstract: Sarcoidosis is a multisystem granulomatous disease of unknown etiology. Pleural involvement is relatively rare. Development of pleural effusion in sarcoidosis needs to be evaluated for other causes, especially tuberculosis in endemic countries. Sarcoid pleural effusion responds to systemic corticosteroids. We are presenting case of 42 year old male patient of sarcoidosis who developed massive pleural effusion while on treatment with steroids, which was attributed to disease per se. Sarcoidosis as a cause of massive pleural effusion has not been mentioned before in published literature.